Metformin pretreatment suppresses alterations to the articular cartilage ultrastructure and knee joint tissue damage secondary to type 2 diabetes mellitus in rats. (3rd May 2020) - Dawood, Amal F.; Alzamil, Norah; Ebrahim, Hasnaa A.; Abdel Kader, Dina H.; Kamar, Samaa S.; Haidara, Mohamed A.; Al-Ani, Bahjat
ABSTRACT: Osteoarthritis (OA) secondary to diabetes affects millions of people worldwide and can lead to disability. The protective effect of metformin pretreatment against alterations to the articular cartilage ultrastructure induced by type 2 diabetes mellitus (T2DM) associated with the inhibition of oxidative stress and inflammation has not been investigated before. Therefore, we induced T2DM in rats (the model group) using high carbohydrate and fat diet and a single injection of streptozotocin (50 mg/kg body weight). The protective group of rats started metformin (200 mg/kg body weight) treatment 14 days before diabetic induction and continued on metformin until the end of the experiment at week 12. Harvested tissues obtained from knee joints were prepared for staining with hematoxylin and eosin (H&E), safranin o staining, and electron microscopy. Histology images showed that OA was developed in the T2DM rats as demonstrated by a substantial damage to the articular cartilage and profound chondrocyte and territorial matrix ultrastructural alterations, which were partially protected by metformin. In addition, metformin significantly ( p < .05) reduced hyperglycemia, glycated hemoglobin (HbA1 c), malondialdehyde (MDA), high sensitivity C-reactive protein (hs-CRP), and interleukin-6 blood levels induced by diabetes. Furthermore, a significant (p ≤ 0.015) correlation between either OA cartilage grade score or the thickness of the articular cartilage and the blood levels of HbA1 c, hs-CRP, MDA, superoxide dismutase (SOD) were observed. These findings demonstrate effective protection of the articular cartilage by metformin against damage induced secondary to T2DM in rats, possibly due to the inhibition of hyperglycemia and biomarkers of oxidative stress and inflammation.